Narrativas sobre a experiência de ensinar a escrever um gênero textual: um estudo fenomenológico - Cardia, Maria Tereza Antonia (2011)
This work is aimed at the understanding of the experience of teaching to write a text genre the opinion article to high school students. In order to do so, five Brazilian-Portuguese language teachers statements were analyzed in this study. These teachers worked with high school students who participated in a national writing competition and were shortlisted as finalists. The statements were presented to the organizers as written practice reports. They are narratives and, as such, are based, on experience, according to Benjamin, (1994). Thus, they constitute a privileged path to access indirectly the experience lived by others. The phenomenological method is considered to be especially adequate to investigate subjective phenomena such as the human experience. The undertaking of the analysis about the narratives was done following this method. The procedures described by Martins and Bicudo, (1989), complemented by Szymanski s, (2004), contributions were adopted for the understanding of the studied phenomenon. Based on immersion into the narratives, seven constellations were revealed and found in most of the statements. This allowed the researcher to elaborate one narrative for each statement. When the five synthesis were gathered, it was possible to recognize new configurations presented in the final synthesis. The discussion on data was enlightened by Arendt s, (2005), ideas. To write a report was a special opportunity for the teachers to reflect upon their practice. The statements indicated that there were many ways to teach, yet all of them were engaged in trying to make the process of learning truly effective. The work done by the teachers was aimed at the improvement of written skills. It was also undertaken as an opportunity to develop a critical view and a commitment to their communities by some of them. It made possible to exercise the multiplicity of perspectives, the strengthening of the feeling of belonging and a concern with the environment. Writing, as well as the opinion article make part of a cultural legacy to which the high school students are entitled because they are new human beings. According to Arendt, (2005), education fulfills its role by bringing high school students in touch with this inheritance, so that they can enjoy it and gradually become responsible for its preservation and renewal